Depression and coping styles of stress in patients with stroke - Barreda S., Dennys (2012)
The stroke is defined as the sudden interruption of blood flow in vessels in any area of the brain. The presence of depression is given with great regularity in those affected. Also, people with more stress are potential candidates for developing stroke. For this reason, this research describe the relationship between depression and stress coping styles, in a sample of 50 stroke patients treated at the outpatient service of neurology at Daniel Alcides Carrion Hospital . For this purpose used the Beck Depression Inventory and Brief COPE-The Coping Estimation Inventory. This research found a statistically significant correlation between the depression´s variables and coping styles to stress avoidance, however there were no significant correlations between the depression´s variables and stress coping styles focused on the problem and emotion respectively.